POSITION OF THE PARTIES IN THE STANDARD AGREEMENT BANKING REVIEWED TO CONSUMER PROTECTION - Yanto, Andra; Syawir, Muhammad; Dainty, Andrew R.J. (SYNTIFIC, 2023)
Background. Along with the increasing world of banking today, especially in the field of credit such as credit buying a car banking business actors increase their development to protect consumers from standard agreements made by business actors. The research aimed to find out the position of the parties in the agreement then leads to problem identification and resolution problem. Research Method. The type of research is doctrinal research, namely, research that analyzes based on laws written in books, journals, and Legal Book Civil And Law Number 8 of 1999 concerning consumer protection. Findings. Article 18 of Law Number 8 of 1999 concerning Consumer Protection, regarding prohibitions inclusion of standard clauses that are detrimental to consumers. The position of the parties within the agreement is reviewed by the Civil Code and laws, and the role of laws in providing protection debtor law as a consumer. Conclusion. Law Number 8 of 1999 addresses debtor risk in credit banking, ensuring standard agreements and private legislators provide legal protection to the debtor as a consumer.